2020
DOI: 10.1007/978-3-030-50519-6_2
|View full text |Cite|
|
Sign up to set email alerts
|

Life Cycle Assessment of a Hydrogen and Fuel Cell RoPax Ferry Prototype

Abstract: Estimates for the greenhouse gas emissions caused by maritime transportation account for approx. 870 million tonnes of CO2 tonnes in 2018, increasing the awareness of the public in general and requiring the development of alternative propulsion systems and fuels to reduce them. In this context, the project HySeas III is developing a hydrogen and fuel cell powered roll-on/roll off and passenger ferry intended for the crossing between Kirkwall and Shapinsay in the Orkney Islands in Scotland, a region which curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In [73], the safety of the alternative marine fuels was also evaluated, considering criteria such as the fuel density, auto-ignition temperature, flammability limits, stoichiometric air-fuel ratio, octane and cetane numbers. It should be noted that recent studies identified hydrogen as the most environmentally friendly alternative marine fuel, supporting the need to produce hydrogen by renewable energy sources [56,66,73,74]. Along the same lines, it is also critical for alternative fuels (e.g.…”
Section: Life Cycle Assessment Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In [73], the safety of the alternative marine fuels was also evaluated, considering criteria such as the fuel density, auto-ignition temperature, flammability limits, stoichiometric air-fuel ratio, octane and cetane numbers. It should be noted that recent studies identified hydrogen as the most environmentally friendly alternative marine fuel, supporting the need to produce hydrogen by renewable energy sources [56,66,73,74]. Along the same lines, it is also critical for alternative fuels (e.g.…”
Section: Life Cycle Assessment Methodsmentioning
confidence: 97%
“…The environmental footprint of a traditional diesel-mechanical and an innovative battery-powered ship was evaluated with an LCA approach in [55], indicating that the use of batteries is not always the optimal solution. Another comparative LCA was presented in [56], identifying ship power plant configurations consisting of hydrogen operated fuel cells and batteries as the most environmentally promising alternative compared to diesel or hybrid systems. However, LCA studies are case-specific and therefore, they fail to capture general trends.…”
Section: Life Cycle Assessment Methodsmentioning
confidence: 99%
“…Thus, in principle ammonia is required to be isolated from any ignition source on-board vessel, when used as a marine fuel. Small fires involving ammonia can be extinguished with dry chemicals or CO2 and large ammonia fires can be extinguished through water spray, fog, or foam emissions [22]. The main risks associated with ammonia are due to its toxic and corrosive nature.…”
Section: Ammoniamentioning
confidence: 99%
“…Moreover, and beyond GHG emissions, a link between particulate matter (PM) emissions from global shipping and health effects was evaluated, with around 60,000 premature deaths estimated annually [50]. For these reasons, many scientific studies and projects are being developed to achieve the target established by the IMO for 2050 using more bio-friendly systems and fuels to decarbonize the sector [51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fuel cells can be also used as an alternative to cold ironing, reducing the emissions at ports [60]. Other projects are focused on hybrid power systems to enhance the transition to cleaner fuels reducing emissions in comparison to original engines [52,[61][62][63]. Furthermore, some companies are developing liquefied H 2 carriers to promote the transport and use of hydrogen in different countries [30,31,64].…”
Section: Introductionmentioning
confidence: 99%